2015
DOI: 10.1166/jnn.2015.9714
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Phase Separation on Bioactivity of Spray Pyrolyzed Bioactive Glass

Abstract: In this study, bioactive glass (BG) particles were synthesized directly using spray pyrolysis (SP). Since the bioactivity of glass particles is well correlated with their chemical composition, how to obtain homogenous bioactive glass becomes an important issue. For SP, the main reason for chemical inhomogeneity was considered to be caused by the difference in the precipitation speed of each precursor. So, two Si-containing precursors of BG, namely tetraethyl orthosilicate (TEOS) and silicon acetate (SiA), have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…So, the formation of amorphous SiO 2 nanoparticles inhibits the formation of HA. This result supports that the view that the addition of a surfactant stabilizes the Si precursor and avoids the formation of amorphous SiO 2 nanoparticles [31] that cause the gas-to-particle conversion for phase separation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…So, the formation of amorphous SiO 2 nanoparticles inhibits the formation of HA. This result supports that the view that the addition of a surfactant stabilizes the Si precursor and avoids the formation of amorphous SiO 2 nanoparticles [31] that cause the gas-to-particle conversion for phase separation.…”
Section: Discussionsupporting
confidence: 88%
“…In a previous study, we used TEOS, CN, and TEP as precursors (Si, Ca, and P precursors, respectively) to prepare SP-derived BG at a high calcination temperature of 700 °C, and the nanoparticles of amorphous SiO 2 and the submicron particles of wollastonite-based glass were observed using TEM and X-ray energy-dispersive spectroscopy [31]. TEOS is insoluble with water because of its hydrolysis behavior, whereas CN and TEP are soluble in water, and the different precipitation behaviors of TEOS, CN, and TEP led to this inhomogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Since the crystallinity of our starting powder is weaker than that of AWGC prepared by Kitsugi et al [19], and the main reason is that the short calcination time of spray pyrolysis (~10 s) at the temperature of 700 • C [20], and AWGCs may not have enough time for crystal growth. For the SEM analysis (see Figure 1b), the starting powder has an average particle size of 0.92 ± 0.44 µm, and the powder exhibits the two typical shapes of a smooth sphere and rough sphere, which is similar to our previous spray pyrolysis study of bioglass [21]. Additionally, the XEDS measurement revealed that the as-prepared powder contained 36.00 ± 1.16 mol% Ca, 9.73 ± 0.02 mol% Mg, 22.09 ± 0.53 mol% P, 31.10 ± 2.17 mol% Si, and 1.08 ± 0.03 mol% F, which is close to the precursor composition.…”
Section: Discussionsupporting
confidence: 80%
“…In the former, micron-sized droplets atomized by an ultrasonic nebulizer are directly converted into oxide particles. In the latter, nano-sized particles (<0.1 μm) condense from the gas phase [28]. Based on the SEM observations, all the surfactant-treated MBG powders had an average particle size of ~600 nm, indicating that all the MBG powders formed via the “one-particle-per-drop” mechanism [27].…”
Section: Discussionmentioning
confidence: 99%